Physical layer security scheme based on power efficient multi-antenna transmitter - Carvalho, Paulo Montezuma (2017)
Security is a demanding challenge in wireless systems due to the broadcast nature of the channel. One the other hand security at physical layer can increase overall system’s security since it can be combined with other security schemes from higher layers. High throughput required by modern wireless networks can be assured by MIMO (Multiple-input multiple-output), but when high spectral efficiencies are needed multilevel modulations with high peak-to-average power ratios should be used, which may affect efficiency of power amplification. This problem can be avoided by the MISO (Multi input Single Output) transmitter considered here, where transmitted multilevel constellations are the result of the combination of several uncorrelated BPSK (Bi-Phase Shift Keying) components, that are amplified and transmitted independently by an antenna. The constellation shaping done by this transmitter means directivity in the transmitted constellation that can be used to assure security at physical layer. Security as well complexity are assured since any eavesdropper must know the set of coefficients associated to each BPSK component as well as the antenna array configuration. It is shown that the inherent security assured by this transmitter allows secrecy at physical layer. Several examples are analyzed and the corresponding results show the effectiveness of the proposed approach to implement a security scheme at physical layer level.